Contrast Sensitivity Deficits and Its Structural Correlates in Fuchs Uveitis Syndrome - Zhou, Fang-Yue; Li, Yi-Sha; Guo, Xingneng; Shi, Xiutong; Wu, Ke; Zheng, Jing-Wei; Li, Xia-Xin; Wu, Jiaqing; Liu, Ruru; Dai, Ma-Li; Huang, Xiu-Feng; Hou, Fang; et al. (Frontiers in Medicine, 2022)
Purpose: To investigate deficits in contrast sensitivity for patients with Fuchs uveitis syndrome (FUS) and to explore the potential relationship between contrast sensitivity and ocular structure. Methods: In this prospective study, 25 FUS patients and 30 healthy volunteers were recruited. Eyes were divided into three groups: FUS-affected eyes of patients (AE), fellow eyes of patients (FE) and healthy eyes. Contrast sensitivity functions (CSF) of all participants were obtained using the quick CSF (qCSF) method. Fundus photographs were collected to evaluate the refractive media, and vascular density (VD) were assessed via optical coherence tomography angiography (OCTA). Data was analyzed and compared using the generalized estimating equation (GEE). Results: CSF were statistically lower for AE compared with FE and Controls. No statistical difference was found between FE and Controls. Contrast sensitivity was negatively correlated with Grading of Haze. No significant correlation was found between visual function and VDs in FUS eyes. Conclusions: We found that the CSF of FUS-affected eyes was reduced, and the visual impairment was predominantly caused by the refractive media turbidity.